2013
DOI: 10.1089/omi.2013.0058
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 Targets Fibronectin 1 to Promote Cell Migration and Invasion in Ovarian Cancer: New Molecular Leads for Therapeutic Intervention

Abstract: Ovarian cancer ranks as the second most common tumor of the female reproductive system, with a large burden on global public health. Therefore, the identification of novel molecular targets and diagnostics is an urgent need for many women affected by this disease. To this end, the human transcription factor SOX2 is involved in a wide range of pathophysiological roles, such as the maintenance of stem cell characteristics and carcinogenesis. To date, in most studies, SOX2 has been shown to promote the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 22 publications
7
61
1
Order By: Relevance
“…Here we demonstrate that SOX2 overexpression influences the migratory potential of NT2/D1 cells, derived from the metastasis of a human testicular germ cell tumor. These results are in accordance with the results obtained with different cancer cells, such as ovarian cancer, breast cancer, glioma, lung cancer, colorectal cancer cells and laryngeal squamous cell carcinoma cell line (Hussenet et al 2010, Lu et al 2010, Alonso et al 2011, Simoes et al 2011, Han et al 2012, Lou et al 2013, Yang et al 2014. In contrast to our result, in the human bladder carcinoma cell line ECV304 ectopic expression of SOX2, OCT4 and NANOG compromised cell motility (Zhou et al 2013), while SOX2 knockdown in U343-MG glioma cell line decreased migration in vitro, but increased the migratory capacity of cancer cells in the brain in vivo (Oppel et al 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Here we demonstrate that SOX2 overexpression influences the migratory potential of NT2/D1 cells, derived from the metastasis of a human testicular germ cell tumor. These results are in accordance with the results obtained with different cancer cells, such as ovarian cancer, breast cancer, glioma, lung cancer, colorectal cancer cells and laryngeal squamous cell carcinoma cell line (Hussenet et al 2010, Lu et al 2010, Alonso et al 2011, Simoes et al 2011, Han et al 2012, Lou et al 2013, Yang et al 2014. In contrast to our result, in the human bladder carcinoma cell line ECV304 ectopic expression of SOX2, OCT4 and NANOG compromised cell motility (Zhou et al 2013), while SOX2 knockdown in U343-MG glioma cell line decreased migration in vitro, but increased the migratory capacity of cancer cells in the brain in vivo (Oppel et al 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Of note, SOX-2 has been shown to target fibronectin 1 to promote cell migration and invasion in ovarian cancer in vitro [21], revealing a regulatory potential of SOX-2 in gynecological cancer. However, although cervical cancer cells overexpressing SOX-2 have been proven to exert enhanced proliferation, clonogenicity, and tumorigenicity [14], the role of SOX-2 in cervical cancer metastasis has not been well established up to date.…”
Section: Discussionmentioning
confidence: 99%
“…Akiyama et al showed that FN1 played a causal role in tumor neovascularization and metastasis (13). In addition, a recent study found that FN1 is one of the key genes in regulating SOX2 cell migration, invasion, colony formation and drug resistance in ovarian cancer cells (14)(15)(16). Qian et al also indicated that FN1 is targeted by let-7g to promote mammary carcinoma cell migration and invasion via p44/42 MAPK and MMPs (17).…”
Section: Discussionmentioning
confidence: 99%